Organizational and Financial Modeling of Transnational Industrial Clusters Sustainable Development: Experience, Risks, Management Innovation - Andreeva, O.V.; Shevchik, E.V. (European research studies, 2017)
The article is devoted to a research of current trends and priorities of organizational and financial modeling of sustainable development. The experience of transnational industrial clusters formation and development is the object of the research. In this article authors conduct a research of the opportunities for sustainable development strategies modeling in the context of new phenomena and precedents, demonstrated by global economic system and revealing in convergence of risk events and divergence of their assessment: new phenomena, properties and characteristics of economic systems, important for the management systems modernization with the purpose to resolve problems of their theoretical and methodological support, had been analyzed; and as a result the method of system and diagnostic analysis, oriented on proactive modeling of management systems competitive performance, was proposed.